Comparing treatments for basal cell carcinoma in terms of long‐term treatment‐failure: a network meta‐analysis. (12th November 2019) - Fukumoto, T.; Fukumoto, R.; Oka, M.; Horita, N.
Abstracts: Although many variations of guidelines have been released, there is limited research that compares multiple treatment strategies for basal cell carcinoma (BCC). The aim of this study was to systematically review the studies reporting on multiple treatments for BCC with systematic review and network meta‐analyses. Search formulas for databases, such as PubMed, EMBASE, Web of Science Core Collection and Cochrane Central Register of Controlled Trials, were created with the support of Cochrane Japan. The patient‐level and tumour‐level meta‐analyses were performed for both the long‐term treatment‐failure and treatment‐success. Of the 1464 studies identified from the database and hand searches, 14 met our inclusion criteria. These 14 studies included 2524 patients and 1738 tumours. Our study indicated that the incidence of treatment‐failure of invasive treatments such as surgery and Mohs micrographic surgery was significantly lower than that of superficial therapies such as cryotherapy, photodynamic therapy, radiotherapy or topical therapies, in the patient‐level and the tumour‐level analyses, despite histological‐type and pretreatment. Relapse of BCC may be a low life‐threatening risk, and there are merits of non‐surgical treatment. However, the significant difference in the recurrence rate is essential. Our study can provide useful guidance to clinicians in selecting treatment options for BCC.